Caracterización psico-pedagógica a partir de la gramática generativa de Chomsky - Vivas Herrera, Jonathan Arturo (2014)
The psycho-pedagogical characterization is performed in this work involves fundamental aspects of generative grammar. Chosmky hard contributed through their research on language and thanks to that, now we can say that any scientific reflection on language is thanks to him. In the first part of a study done on the various grammars that precede the formation of generative grammar and thereafter are considered valuable for the development of this thesis elements. At this time renowned authors who have studied the language as a specific power of the human being and which is conceived as a communication be displayed. In the second part of a comparison between terms or concepts of generative grammar and constructivist psychology, so you can make connections that become applicable to the current education runs. It is equally important to note that both psychology and linguistics come together to forge psycholinguistics and that this serves to understand the processes within the brain, through its use by the neurosciences. Finally, the applicability of psycho-pedagogical in the field of pedagogy components, focusing on the learner as an active subject of knowledge is conceived. Currently working with the constructivist in education accordingly and, above all, the main actor in the educational process is the learner. These elements will improve the teaching-learning relationship.